ACSM's Clinical exercise physiology - Thompson, Walter R. (Philadelphia : Wolters Kluwer, 2019)
ACSM's Clinical Exercise Physiology adapts and expands upon the disease-related content from ACSM's Resource Manual for Guidelines for Exercise Testing and Prescription, 7th Edition, to create a true classroom textbook. This new resource offers research-based coverage of more than 35 conditions commonly seen in practice—from a host of cardiovascular disorders to immunological/hematological disorders. Condition chapters are organized by disease types and then divided into sections that cover specific conditions from a pathological and etiological perspective. To provide a complete view of clinical exercise physiology, the book also covers important considerations and foundational elements, such as screening, pharmacology, and electrocardiography. As an American College of Sports Medicine publication, the text offers the unsurpassed quality and excellence that has become synonymous with titles by the leading exercise science organization in the world.eBook available. Fast, smart, and convenient, today's eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and much more.Complete alignment with the latest ACSM's Guidelines ensures focused coverage of all essential topics.Evidenced-based coverage of over 35 conditions provides the most extensive coverage of diseases available for the course. A standard format in the conditions chapters (introduction, condition, pathology, clinical applications, case study, summary, and comorbidities case studies) makes specific information easy to find.A chapter on exercise genomics provides an overview of this new field and its potential clinical applications, while a separate chapter on electrocardiography provides a solid foundation for those who need to read and interpret EKGs. Special considerations beyond the conditions, such as comorbidities, the exercise environment, legal considerations, lifespan considerations, pharmacology, etc. ensure complete coverage of clinical exercise physiology.In-text learning aids, including chapter-opening summaries and learning objectives, end-of-chapter review questions and case studies with questions for classroom discussion, help students prepare for practice.
Includes index.
Keywords: Exercise -- Physiological aspects; Sports medicine; Exercise Therapy -- Practice Guideline; Exercise -- physiology -- Practice Guideline